2020
DOI: 10.1111/1759-7714.13557
|View full text |Cite
|
Sign up to set email alerts
|

Poor efficacy of anti‐programmed cell death‐1/ligand 1 monotherapy for non‐small cell lung cancer patients with active brain metastases

Abstract: Background The efficacy of anti‐programmed cell death‐1/ligand 1 antibody monotherapy (anti‐PD‐1/PD‐L1 monotherapy) in patients with active brain metastases (BMs) is not established. Here, we aimed to evaluate the efficacy of anti‐PD‐1/PD‐L1 monotherapy in non‐small cell lung cancer (NSCLC) patients with active BMs. Methods This retrospective study included NSCLC patients treated with second‐line or later‐line anti‐PD‐1/PD‐L1 monotherapy between December 2015 and August 2019. Patients were classified into thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“… 27 The iORR was 62.5% in 11 patients who had not received local radiotherapy, indicating tremendous potentials of ICIs for BM in patients with previously untreated NSCLC and high PD‐L1 expression. However, Tozuka et al 28 showed a poor iORR of 13.3% for anti‐PD‐1/PD‐L1 antibody monotherapy in 15 NSCLC patients with active BM. This may be because of the high proportion of patients with PS >2 (38%) and EGFR or ALK mutations (25%) who may have a low response to immunotherapy.…”
Section: Discussionmentioning
confidence: 98%
“… 27 The iORR was 62.5% in 11 patients who had not received local radiotherapy, indicating tremendous potentials of ICIs for BM in patients with previously untreated NSCLC and high PD‐L1 expression. However, Tozuka et al 28 showed a poor iORR of 13.3% for anti‐PD‐1/PD‐L1 antibody monotherapy in 15 NSCLC patients with active BM. This may be because of the high proportion of patients with PS >2 (38%) and EGFR or ALK mutations (25%) who may have a low response to immunotherapy.…”
Section: Discussionmentioning
confidence: 98%
“…All predictors were evaluated and recorded when the patient was suspected of LM. Active brain metastases was defined as concomitant untreated or progressed brain metastases ( 14 16 ). Progressed extracranial disease means disease progression (limited to extracranial lesions) evaluated by clinicians according to RECIST 1.1 ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
“…Considering the heterogeneity of cancer, more research is needed regarding the relationship between BBB permeability and intracranial efficacy of ICIs. Clin Lung Cancer [32] Pembrolizumabbased therapy 0 (0) 0 (0) 3 (42.9) 4 (57.1) 4 (57.1) 3 (42.9) 6 Thorac Cancer [27] PD- Lung Cancer [35] Nivolumab monotherapy 2 (40.0) 0 (0) 0 (0) 3 (60.0) 5 (100.0) 0 (0) 9 Lung Cancer [28] Nivolumab monotherapy…”
Section: Association Between Penetration Of Ici Across the Bbb/btb An...mentioning
confidence: 99%